Un nuevo objeto. La literatura en la época de la inespecificidad del cine - Emilio Bernini (Cuadernos LIRICO)
After having found in literature a narrative source and an aesthetic legitimation, the cinema of the sixties consecrated its autonomy by assuming the notions of author and writing. From the nineties onwards, cinema began to lose its specificity; its relations with literature ceased to be homogeneous. A new object appears with the study of the poetics of Gustavo Fontán, who gives a tactile dimension to vision, and of Albertina Carri, who finds in words ways of diminishing the prepotence of images. From their diversity, both reveal today the lack of specificity of cinema in its relations with other arts, including literature.